Ovarian involvement of epithelioid trophoblastic tumor: A case report - Khunamornpong S. (2014)
Epithelioid trophoblastic tumor (ETT) is an uncommon type of gestational trophoblastic neoplasia originating from the chorionic-type intermediate trophoblast. To our knowledge, ovarian involvement of ETT with initial presentation as an ovarian tumor has not been reported. A 32-year-old woman presented with a 9-cm left ovarian mass. No clinical evidence of uterine involvement was identified at diagnosis or follow-up. The patient had a previous history of hydatidiform mole treated with suctional curettage 5 years before. Ovarian involvement of ETT can be challenging to pathologists and may be potentially confused with ovarian epithelial carcinoma, particularly of clear cell differentiation. © 2011 International Society of Gynecological Pathologists.